Dipyridamole potentiates the inhibition by 3'-azido-3'-deoxythymidine and other dideoxynucleosides of human immunodeficiency virus replication in monocyte-macrophages. - Szebeni, J (1989)
Dipyridamole (DPM) is commonly used as a coronary vasodilator and inhibitor of platelet aggregation in the treatment of cardiovascular diseases. We report here that DPM potentiates the inhibitory effects of 3'-azido-3'-deoxythymidine (AZT) and 2',3'-dideoxycytidine against human immunodeficiency virus type 1 (HIV-1) in human monocyte-macrophages. At the same concentrations, DPM does not potentiate the toxic effects of AZT on these cells or on human bone marrow (granulocyte-monocyte) progenitor cells. Since monocyte-macrophage lineage cells appear to be the major reservoir for HIV-1 in vivo, these findings suggest the possibility of using DPM or its analogues in combination chemotherapy of HIV infections.